2020
DOI: 10.1590/1806-9282.66.12.1666
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of memory T cells in COVID-19 patients and the predictive role of CD4+CD8+ double positive T lymphocytes as a new marker

Abstract: SUMMARY BACKGROUND: The COVID-19 pandemic has affected the entire world, posing a serious threat to human health. T cells play a critical role in the cellular immune response against viral infections. We aimed to reveal the relationship between T cell subsets and disease severity. METHODS: 40 COVID-19 patients were randomly recruited in this cross-sectional study. All cases were confirmed by quantitative RT-PCR. Patients were divided into two equivalent groups, one severe and one nonsevere. Clinical, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(17 reference statements)
0
16
1
1
Order By: Relevance
“…TCD4 cells play an essential role in the immune response by helping TCD8 and B cells to produce antibodies [ 44 ]. Various investigations have indicated that in patients with severe COVID-19, both TCD4 and TCD8 are reduced [ 45 ]. In our study, both TCD4 and TCD8 cells were recovered after cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TCD4 cells play an essential role in the immune response by helping TCD8 and B cells to produce antibodies [ 44 ]. Various investigations have indicated that in patients with severe COVID-19, both TCD4 and TCD8 are reduced [ 45 ]. In our study, both TCD4 and TCD8 cells were recovered after cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…T-cells are one of the most important components of the immune system against viral disease [ 33 ]. Studies have shown that the number of CD4+ and CD8+ T-cells is reduced in patients with severe COVID-19 infections [ 34 ]. In our study, there were no significant changes in the number of CD4+ and CD8+ cells, 24 h after cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…and fibrinogen [23]. In addition to inflammatory serum markers, it was shown that variations in blood leukocytes counts are significantly affected in patients with severe COVID-19, especially in non-survivors [17].…”
Section: Discussionmentioning
confidence: 99%